Reheating after Gauss-Bonnet inflation - L, Bum-Hoon; T, Gansukh (Scientific transaction of the National University of Mongolia. Physics, 2022)
The physics of reheating after cosmic inflation is highly uncertain and unconstrained hence it is strongly model dependent. However, the duration of reheating and thermalization temperature at the end of reheating can be determined in terms of the equation-of-state parameter. By considering the chaotic inflation with the monomial coupling, we attempt to determine the equation-of-state parameter during reheating. Our result shows that !th > 1=3 is preferred in order for successful inflation to occur. Moreover, reheating lasts longer in our model and predicted reheating temperature at the end of reheating is lower than the standard scenario. PACS numbers: 95.35.+d